Philosophical Values of Educational Globalization at Bina Insan Mulia Islamic Boarding School - Gufron, Iffan Ahmad; Barnawi, Barnawi (Eduprof : Islamic Education Journal, 2025)
Globalization of education provides challenges and opportunities for traditional educational institutions, including Islamic boarding schools, to remain relevant amidst changing times. This study explores the philosophical values ​​of globalization of education applied at the Bina Insan Mulia Islamic Boarding School. This Islamic boarding school integrates Islamic values-based education with a modern approach to facing global demands. The research method uses a qualitative approach with in-depth interview techniques, observation, and document analysis. The research was conducted from August 2024 to October 2024, with the caretakers of the boarding school, educators, and students as informants. The data analysis technique used was thematic analysis, exploring patterns and relationships between various educational elements that reflect the values ​​of globalization. The study results indicate that the Bina Insan Mulia Islamic Boarding School has succeeded in internalizing universal values ​​such as tolerance, inclusiveness, and transmission through a Islamic Boarding School-based curriculum combined with a global education program. The philosophical values ​​include harmony between local traditions and modernity, the formation of globally oriented student characters, and a commitment to cultural diversity. This study confirms that Islamic boarding schools can be an adaptive and innovative educational model in the era of globalization without losing their cultural identity.